Business Model Innovation as Strategic Renewal Process: A Case of China's Most Innovative Firm - Musa, S M; Mamun, Syed A. (UUM Press, 2018)
To survive in today's hypercompetitive business environment, firms from every sector must rely on innovation. Innovation is one of the main drivers of a firm's strategic renewal process. Strategic renewal process often calls for business model renewal which is only possible through business model innovation. Business model innovation is relatively new concept in business literature. This article is an attempt to highlight the business model innovation process of one of the most innovative firms of our time from China. Over the last thirty years, this firm went through multiple strategic renewal processes by reinventing its business model inspired by the technological changes. In doing so, this firm aims to change the whole white goods manufacturing industry as we know it today.